TEACHERS' ROLE IN FOSTERING A MODERATE, NATIONALIST GENERATION THROUGH HABITUATION AT SMP ISLAM MANBA’UL ULUM BUARAN JEPARA - Muhammad Dhiyaul Haq; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the strategic role of teachers in shaping a moderate and nationalist generation through school culture habituation programs at SMP Islam Manba’ul Ulum Buaran Jepara. Utilizing a qualitative approach with a case study design, data were gathered through interviews, observations, and documentation, and then validated using data triangulation. The results indicate that the teachers' role has transformed from merely instructors into role models and embedded supervisors. Teachers systematically integrate moderate (wasathiyyah) Ahlussunnah wal Jama’ah Islamic religiosity and nationalistic spirit (nasionalisme) into school culture management through two main pillars: 1) School Culture-Based Routine Habituation Program: Facilitated by direct teacher guidance during the recitation of Nadham Aqidatul Awam & Asmaul Husna, congregational dhuha prayer, the tradition of handshaking, and post-dawn murojaah of the Qur'an to strengthen a tolerant (tawasuth) faith, the character of respect (ta'dzim), and a rahmatan lil 'alamin (blessing to all creation) mentality; 2) Value Internalization through Extracurricular Activities: Functioning as a social laboratory to balance students' intelligence through the dimension of Islamic cultural arts adaptive to local wisdom (Qiro'ah, Nasyid, Rebana, Calligraphy), the physical-sporting dimension of state defense (Volleyball, Scouts, Pencak Silat), and the digital literacy dimension (Computer). This integrative synergy is proven effective in breaking down the dichotomy between religious and national values, while simultaneously safeguarding students from the negative impacts of globalization and radicalism.